2021
DOI: 10.1101/2021.07.16.452631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

From computing transition probabilities to word recognition in sleeping neonates, a two-step neural tale

Abstract: Extracting statistical regularities from the environment is a primary learning mechanism, which might support language acquisition. While it is known that infants are sensitive to transition probabilities between syllables in continuous speech, the format of the encoded representation remains unknown. Here we used electrophysiology to investigate how 31 full-term neonates process an artificial language build by the random concatenation of four pseudo-words and which information they retain. We used neural entr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Regarding statistical learning, several studies have indeed shown that neonates, at least at term age, are sensitive to conditional statistics between syllables. For example, they use transition probabilities between syllables to discover words in an artificial stream composed of four randomly concatenated tri-syllabic non-words (Teinonen, Fellman, Naatanen, Alku, & Huotilainen, 2009;Kudo, Nonaka, Mizuno, Mizuno, & Okanoya, 2011;Fló, Benjamin, Palu, & Dehaene-Lambertz, 2021; see also Benjamin et al, 2021 for quadrisyllabic words). Because any of the three other words can follow a given word, there is a drop in transition probability between syllables at the end of the word, from 1 within a word to 0.33 between words.…”
Section: Both Preterm and Full-term Neonates Learn An Alternation Reg...mentioning
confidence: 99%
“…Regarding statistical learning, several studies have indeed shown that neonates, at least at term age, are sensitive to conditional statistics between syllables. For example, they use transition probabilities between syllables to discover words in an artificial stream composed of four randomly concatenated tri-syllabic non-words (Teinonen, Fellman, Naatanen, Alku, & Huotilainen, 2009;Kudo, Nonaka, Mizuno, Mizuno, & Okanoya, 2011;Fló, Benjamin, Palu, & Dehaene-Lambertz, 2021; see also Benjamin et al, 2021 for quadrisyllabic words). Because any of the three other words can follow a given word, there is a drop in transition probability between syllables at the end of the word, from 1 within a word to 0.33 between words.…”
Section: Both Preterm and Full-term Neonates Learn An Alternation Reg...mentioning
confidence: 99%
“…Since data from 8 children were rejected due to insufficient artifact-free trials in the EEG task, the final sample consisted of 25 infants (12 males; mean age = 8.00 months; in days, M = 240.16, SD = 19.13,min = 208,max = 279). Sample size was determined based on the previous SS-EP literature in similar populations (Kabdebon et al, 2015;Cirelli et al, 2016;Peykarjou et al, 2017;Choi et al, 2020;Fló et al, 2022). Information about parents' and children's daily exposure to music was collected, in order to better characterize the sample from this point of view.…”
Section: Participantsmentioning
confidence: 99%
“…Importantly, it offers an objective definition of the targeted responses: based on the frequency of the stimulation, SS-EPs are expected at a specific narrow frequency band (Zhou et al, 2016). Previous studies on newborns and infants applied frequency-tagging paradigms with periodic visual stimulation to investigate face and object processing (e.g., de Heering and Rossion, 2015;Peykarjou et al, 2017;Buiatti et al, 2019), and with rhythmic speech sounds to investigate the tracking of transitional probabilities in the context of artificial grammar learning (Kabdebon et al, 2015;Choi et al, 2020;Fló et al, 2022).…”
Section: Introductionmentioning
confidence: 99%